PLAN DE SEGURIDAD INDUSTRIAL Y SALUD OCUPACIONAL PARA LA EMPRESA “TORNERÍA IÑIGUEZ”, DE LA CIUDAD DE PIÑAS, PROVINCIA DE EL ORO - Loaiza Iñiguez, Jessica Marlene (2020)
The Industrial Safety and Occupational Health Plan for Turnería Iñiguez, was carried out with the purpose of preparing a proposal for an Industrial Safety and Occupational Health Plan to guide the company in complying with current regulations and improve working conditions for workers With the use of the descriptive method, the current situation of the company was detailed, identifying the occupational risks and preventive measures to later identify strengths and weaknesses. Three techniques were used: survey of the seven workers, interview with the Manager-Owner, and direct observation based on the checklist of compliance with legal regulations on safety and health at work. In the diagnosis of the current situation and identification of risks, the following results were obtained: 100% of the workers have personal protective equipment; the main risks to which they are exposed are mechanical such as: entrapment with machinery, cuts, burns, etc; physical: fires, explosions, ultraviolet radiation, among others; and chemicals: inhalation of dusts, aerosols, corrosive substances and others; For this reason, 71.43% have suffered work incidents such as burns, cuts, blows; while 28.57% have suffered occupational accidents: projection of particles to the eyes, cuts due to the manipulation of a grinder; 57.14% consider that the level of risk due to the manipulation of machinery or tools is high; Regarding document management, the delegate for Occupational Health and Safety has not been appointed, there is no Occupational Health and Safety policy, the risk register and action plan have not been drawn up, there is no a training plan and there is no workers' health surveillance registry. The owner is recommended to execute the plan, which will help to comply with the regulations avoiding penalties, will benefit workers in their safety and health, having a work environment in optimal conditions would increase productivity, reducing costs and interruptions in work activity and it would improve the image of the company by demonstrating compliance with corporate social responsibility.